Enriching Athlete-Environment Interactions in Youth Sport: The Role of a Department of Methodology - Keith Davids; Martyn Rothwell; Sam Hydes; Tim Robinson; Charlie Davids (MDPI AG, 2023)
The aim of this insights paper is to propose how the theory of ecological dynamics may invite re-consideration of how sport scientists could support performance, learning and development of children and youth in sports programmes. We seek to outline why learning should be individualised and contextualised, based on the specific needs of learners, such as children and youth, women and disabled athletes in sport. Case examples from individual and team sports are presented to illustrate how constraints can be designed to enrich interactions of children and youth with different performance environments, based on integrating principles of specificity and generality in learning and development. These case examples suggest how a collaborative effort by sport scientists and coaches in children and youth sport may be undertaken in a department of methodology to enrich learning and performance.